THE EFFECT OF DIGITAL MARKETING ON THE DECISION TO PAY ZAKAT THROUGH ZAKAT INSTITUTION - Harnie Agustina; Mukhamad Najib; Rahmat Mulyana (Department Islamic Economics, 2022)
Purpose-To find out the digital marketing strategies carried out by Zakat Institution and to find out the effect of digital marketing on the decision to pay zakat at the Zakat InstitutionDesign/methodology/approach-This research used quantitative descriptive analysis method. Questionnaires divided into 2 categories, 77 respondents have already paid zakat at Zakat Institution (referred as Muzakki) and 94 respondents have never paid zakat through Zakat Institution (referred as Non-Muzakki). The analysis method used Structural Equation Modeling Partial Least Squares (SEM-PLS).Findings-The variables affecting Non-Muzakki and Muzakki to pay zakat through Zakat Institution were the same, namely social media marketing, customer engagement, and brand trust. The fundamental difference in the factors influencing the decision to pay zakat between Muzakki and Non-Muzakki was brand trust, where Non-Muzakki were more concerned about brand trust than Muzakki.Research Implications-Marketing content and accessibility in the digital marketing conducted by Zakat Institution did not significantly affect the decision to pay zakat. Factor differentiating between Muzzaki and Non-Muzzaki was brand trust. This is important to note, so consumers believe that zakat collection can be distributed to the Mustahiq/Beneficiaries to assist their livelihood. Zakat Institution must demonstrate social responsibility through the distribution of Zakat and the implementation of Corporate Social Responsibility as a form of concern to the surrounding community.Originality-The study determined the factors affecting the decision to pay zakat through digital marketing by comparing between muzzaki and non-muzzaki.Keywords-Digital, Marketing, Zakat, Institution, Zakat institution, Consumer behavior.I